Investigation of mechanical, durability, and thermal properties of sustainable self-compacting mortars containing construction demolition waste and supplementary cementitious materials - Culcu, Muzeyyen Busra; Esen, Hikmet (Elsevier, 2024)
This study aims to produce sustainable self-compacting mortar (SSCM) to provide solutions to the waste generation caused by the construction industry and to provide alternative solutions to the increasing consumption of natural resources and cement. In SSCM designed as 12 different mixtures; recycled sand (RCS) and pumice were used as aggregate and silica fume (SF) and fly ash (FA) were used as supplementary cementitious materials (SCM). The mechanical, durability, and thermal properties of the produced SSCM were investigated. Compressive and flexural strengths were determined at age of 7, 28 and 90 days. Significant increases in flexural and compressive strengths were observed for 10 % SF and 10 % FA substitutions. After 90 days of water curing, the specimens were exposed to high temperature. A decrease of up to 93.4 % in flexural strength was observed after high temperature effect. Sorptivity, water absorption and porosity values were determined. Thermal conductivity test was also performed on the specimens. Significant changes were observed due to the use of SCM. The global warming potential (GWP), and energy consumption (EC) were considered to evaluate environmental properties. Significant reductions in GWP and EC values were observed for mortar series with 30 % SCM. Significant gains were achieved in economic properties due to the use of SCM, with total costs decreasing by approximately 10 %, especially in series with 30 % SCM. SSCM produced using recycled aggregates and SCMs have provided significant contributions to sustainability.
Keywords: Sustainability; Construction and demolition waste; Supplementary cementitious materials; Self-compacting mortars; Thermal conductivity